TINJAUAN PELAKSANAAN PENGADAAN BARANG DAN JASA - Edah Jubaedah; Efan Suprastiyo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
PT. PINDAD (PERSERO) is a State-Owned Enterprise (BUMN) which is engaged in the weapons industry, providing the main equipment needs for weapons systems independently to support the implementation of equipment and security for the Republic of Indonesia in order to implement and support policies in the field of economy and national development. To achieve the company's vision and mission, one of its divisions is the Supply Chain Division, which functions in the procurement of goods and services that can provide added value to the company. In the process of procuring goods and services carried out by the Supply Chain Division, there are several problems that slow down the procurement process, including problems related to: Delay in delivery of materials and goods (diameter tools), Self Estimated Prices (HPS) using old data. Efforts are being made to overcome problems from vendors, namely: if the vendor has experienced complaints related to reasonable delays in goods, the company will not give sanctions, but if the delays in goods are unreasonable, applicable sanctions will apply. If the vendor cannot complete the order on time, the vendor will be re-elected or make another procurement to another vendor who is able to complete the order and coordinate with the user. Meanwhile, the effort to overcome the problem of Self Estimated Price (HPS) is that the user conducts a survey to the field regarding the price or through electronic media. With the above efforts, it is hoped that PT. PINDAD (PERSERO) Supply Chain Division can solve vendor problems and Self Estimated Prices (HPS), so that the procurement of goods or materials in the Supply Chain Division runs smoothly.